Contingency Management for Patients with Cooccurring Disorders: Evaluation of a Case Study and Recommendations for Practitioners - Claire E. Adams; Carla J. Rash; Randy S. Burke; Jefferson D. Parker (Case Reports in Psychiatry, 2012)
Research indicates that contingency management (CM) has potential to improve a number of outcomes (e.g. substance use, treatment attendance, quality of life) among individuals with substance use and cooccurring disorders. However, multiple factors must be considered on a case-by-case basis in order to promote optimal treatment effects. The present study describes an individualized CM protocol for a US Veteran with substance dependence and cooccurring severe mental illness. CM targeted attendance at outpatient appointments and appropriate use of hospital resources. Effects of CM were assessed by comparing the 3-month baseline and CM periods. The CM intervention marginally reduced unnecessary hospital admissions, resulting in cost savings to the medical center of over $5,000 in three months for this individual. However, CM did not affect outpatient attendance. Several complications arose, highlighting challenges in using CM in populations with substance use and cooccurring disorders. Practical suggestions are offered for maximizing the effects of CM.